Abstracts of the First Joint Meeting AMEVASC/SIECV ictus2021 (Ictus, 2022)
Abstracts of the first joint annual meeting "ictus2021" of  the "Asociación Mexicana de Enfermedad Vascular Cerebral (AMEVASC)" and the " Sociedad Iberoamericana de Enfermedades Cerebrovasculares (SIECV)" in October 2021.
Keywords: stroke; cerebrovascular diseases; abstracts